KNOWLEDGE ATTITUDE AND PRACTICE OF DENTAL STUDENTS TOWARDS FINISHING AND POLISHING OF COMPOSITE RESTORATION. (Journal of Pharmaceutical Negative Results, 2022)
Introduction: In the direct restorative method we have to observe numerous steps to obtain aesthetic, natural and predictable results. It's important to achieve the finishing and polishing process and supply the composite resin with a natural look of tooth gloss. The first step of finishing and polishing is checking and correcting the shape of the tooth. The shape is liable for the symmetrical percentage and integration of the restoration with the numerous teeth. The aim of this study is to evaluate the knowledge, attitude and practices of dental students towards finishing and polishing of composite restoration.Materials and methods : Self-administered questionnaire as designed On the topic “knowledge, attitude and practices towards finishing and polishing of composite restoration among dentists '' The questionnaire was distributed through a google forms link.The entered data analysed using SPSS statistics Version 21.0. Descriptive statistics was performed to calculate frequencies of categorical variables and chi square test was done to study the association.Results: Majority of respondents had good knowledge (67.5%), while 60.5% of them had good practices. After controlling for confounders by multivariate logistic regression, all categories of dentists with good knowled ge and consultants still had significantly better dental practices.P = 0.58 > 0.05. Conclusion: Experienced dentists and restorative consultants appear to have adequate knowledge about composite and this had a significant impact on their practice. A need however exists to bridge the gap among other categories of dental personnel to improve the esthetic outcome of composite restorations.